Understandings of nature and grace in John Milbank and Thomas Aquinas - Mawson, Michael (Scottish journal of theology, 2009)
John Milbank is one of the most recent and arguably most radical proponents of an understanding of nature as graced. This article critically examines Milbank's understanding of nature and grace, specifically as elaborated within his reading of Thomas Aquinas. In the first part I will outline Aquinas's most direct discussions of nature and grace in the Summa Theologica, drawing attention to several central, albeit subtle, distinctions that these contain. In the second and third parts, I will examine Milbank's reading of Aquinas in Truth in Aquinas, and examine whether it adequately reflects and negotiates Aquinas's distinctions. On this basis I will argue Milbank's reading, while drawing attention to some important and often neglected areas of Aquinas's thought, ultimately remains limited.